Computational Identification of Amino-Acid Mutations that Further Improve the Activity of a Chalcone–Flavonone Isomerase from Glycine max - Yuan, Hui; Wu, Jiaqi; Wang, Xiaoqiang; Chen, Jiakuan; Zhong, Yang; Huang, Qiang; Nan, Peng (Frontiers in Plant Science, 2017)
Protein design for improving enzymatic activity remains a challenging work in biochemistry, especially to identify target amino-acid sites for mutagenesis and to design benefit mutations for those sites. Here we employ a computational approach that combines multiple sequence alignment, positive selection detection, and molecular docking to identify and design benefit amino-acid mutations that further improve the intramolecular-cyclization activity of a chalcone-flavonone isomerase from Glycine max (GmCHI). By this approach, two GmCHI mutants with higher activities were predicted and verified. The results demonstrated that this approach could determine the benefit amino-acid mutations for improving the enzymatic activity, and may find more applications in engineering of enzymes.